2008
DOI: 10.1158/0008-5472.can-07-5687
|View full text |Cite
|
Sign up to set email alerts
|

Fhit-Deficient Hematopoietic Stem Cells Survive Hydroquinone Exposure Carrying Precancerous Changes

Abstract: The fragile FHIT gene is among the first targets of DNA damage in preneoplastic lesions, and recent studies have shown that Fhit protein is involved in surveillance of genome integrity and checkpoint response after genotoxin exposure. We now find that Fhit-deficient hematopoietic cells, exposed to the genotoxin hydroquinone, are resistant to the suppression of stem cell in vitro colony formation observed with wild-type (Wt) hematopoietic cells. In vivo-transplanted, hydroquinone-exposed, Fhit-deficient bone ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…We have reported previously that Fhit is involved in the DNA damage response through modulation of checkpoint proteins (Ishii et al, 2008; Okumura et al, in press). To determine if Nit1 may also have a role in responses to DNA damage, we examined the expression of γH2AX and pChk2 in wt, Fhit −/− and DKO non-neoplastic tissues of treated and non NMBA-treated mice; pChk2 and γH2AX were expressed in NMBA-treated Fhit −/− , non-treated and treated DKO forestomach tissues, but not in untreated Fhit −/− tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported previously that Fhit is involved in the DNA damage response through modulation of checkpoint proteins (Ishii et al, 2008; Okumura et al, in press). To determine if Nit1 may also have a role in responses to DNA damage, we examined the expression of γH2AX and pChk2 in wt, Fhit −/− and DKO non-neoplastic tissues of treated and non NMBA-treated mice; pChk2 and γH2AX were expressed in NMBA-treated Fhit −/− , non-treated and treated DKO forestomach tissues, but not in untreated Fhit −/− tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in intracellular levels of ROS are detected in FHIT negative BMCs relative to wild-type, and this reduction in ROS accumulation is linked to failure to induce apoptosis as the phenotype is reversed with application of the antioxidant N-acetyl-L-cysteine. 1,5,[7][8][9]69 Several studies that connect Fhit expression to increased sensitivity to anti-cancer drugs may also serve to substantiate the link between Fhit function and oxidative stress. Re-expression of Fhit in Fhit-negative cancerderived cell lines increases sensitivity to mitomycin C (MMC), camptothecin (CPT), and cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of cells that have lost FHIT revealed that the protein has some functional roles in response to DNA damage (Saldivar et al, 2010). In particular, kidney epithelial cells established from Fhit-/-mice exhibited >2-fold increased chromosome breaks at fragile sites vs. corresponding Fhit+/+ cells (Turner et al, 2002), and the frequency of mutations following replicative and oxidative stress in Fhit-deficient cells was 2 to 5-fold greater than in Fhit-expressing cells (Ishii et al, 2008;Ottey et al, 2004). Despite these findings and strong evidence that Fhit acts as a tumor suppressor (Joannes et al, 2010;Pekarsky et al, 1998;Siprashvili et al, 1997) it has been proposed that deletions within the FHIT locus are secondary alterations rather than cancer-driving mutations (Bignell et al, 2010).…”
Section: Recent Developmentsmentioning
confidence: 99%